Les futurs enseignants et la didactique du français écrit: l’impact de la compétence perçue et réelle sur l’évolution des représentations à propos de la langue et de son enseignement - LeFrancois, Pascale; Montesinos-Gelet, Isabelle (Canadian Journal of Higher Education, 2005)
The purpose of this article is to describe the evolution of student teachers' representations on written French, according to their linguistic competence and to the appropriateness of their perceived competence in French. To achieve this, a survey was filled in twice by 67 students taking a first-year university course on grammar teaching, at the beginning and the end of the semester. This survey assessed beliefs about ten topics covered during the course. In general, after the course, students' representations have changed, in a way that varies according to the beliefs considered. Linguistic competence influences the ability to make one's representations evolve positively: the more one is competent in written French, the more one perceives one's competence correctly, the more one is open to the training given through the course; the less one is competent in written French, the more one overestimates one's competence, and the less one benefits from the course to make one's representations evolve. These results are particularly important in order to build a successful training program for student teachers.